1970
DOI: 10.3329/ujzru.v26i0.703
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stages of red the spider mite, <i>Oligonychus coffeae</i> Neitner (Acari: Tetranychidae) infesting rose

Abstract: :The experiment was conducted to study the duration of different developmental stages of Oligonychus coffeae Nietner in six generations in different seasons of the year. The eggs of O. coffeae developed to adult within the shortest duration of 5.30±0.16 days at 30.28°C and 76.00% RH in June, but it took 12.91±0.21 days at 19.80°C and 75.41% RH in January. The highest temperature accelerated the developmental rate and reduced the duration of developmental stages. Temperature exerted significant effect on all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 1 publication
6
7
4
Order By: Relevance
“…According to him, total time taken to complete the life cycle was 12.97 days. For the other stages, like incubation period, larval period and protonymphal periods, the present findings also disagree with the results of Haque et al (2007). There were substantial differences, as becomes evident from the fact that the duration of these periods was 7.03, 2.13 and 1.83 days, respectively (Haque et al, 2007) contrary to 2.47, 5.4 and 6.4 days, respectively (as observed in the present study).…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…According to him, total time taken to complete the life cycle was 12.97 days. For the other stages, like incubation period, larval period and protonymphal periods, the present findings also disagree with the results of Haque et al (2007). There were substantial differences, as becomes evident from the fact that the duration of these periods was 7.03, 2.13 and 1.83 days, respectively (Haque et al, 2007) contrary to 2.47, 5.4 and 6.4 days, respectively (as observed in the present study).…”
Section: Resultscontrasting
confidence: 85%
“…The present investigation revealed that the total time taken to complete the life cycle (egg to adult) was 16.17 days at 20°C and 65% RH on tea leaves. As regards the time required for development from egg to adult, the results of the present investigation disagrees with the results of Haque et al (2007), who worked on the biology of Oligonychus coffeae infesting rose at 19.80°C and 65.5% RH. According to him, total time taken to complete the life cycle was 12.97 days.…”
Section: Resultscontrasting
confidence: 84%
“…The regression coefficient (b yx = -0.016) shows that, for 1% increase, the relative humidity would decrease the population of mite by 0.02 per leaf. The results of present studies were similar to the results that the increase in relative humidity results in the decline in the mites population (Linger et al, 1998;Gillispie et al, 2000;Haque et al, 2007).…”
Section: Relative Humidity V/s Population Of Mite (Tetranychus Urticasupporting
confidence: 94%
“…The regression coefficient (b yx = -0.098) suggested that, for each unit, the increase in the mean temperature would decrease the thrips population by 0.10 per leaf. The results on the average population of mite recorded on 10 varieties of mung bean from June 14 to August 29, 2005 at weekly intervals are displayed in Table 2 Haque et al (2007) reported that Tetranychus urticae growth and development were correlated with the increase in temperature, i.e., the development time was reduced with the increase in temperature and decrease in relative humidity. Gillispie et al (2002) reported that temperature and relative humidity affected the development of Tetranychus mites.…”
Section: Resultsmentioning
confidence: 97%
“…The total development time of O. oryzae decreased over the temperature range of 20-35 °C. Similar results were given by Haque et al, (2007) on Oligonychus coffeae (Nietner) and Sakunwarin et al, (2003) on T. truncatus. Boudreaux (1963) mentioned that the development time decreased for each developmental stage as temperature increased and was common for tetranychid mites while the most rapid development of many spider mite species occurred between 20 and 29 °C which agreed with the results of this study.…”
Section: Duration Of Development Instars Of O Oryzaesupporting
confidence: 86%